A novel irrigation device with superior nasal irrigation efficiency to the classic rinse bottle - Dawei Wu; Feifan Chang; Junsheng Hong; Baihan Su; Yongxiang Wei (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background The ability of saline irrigation to detach the mucous and the flow-limiting effect of the nasal valve has not been well explored. The objective of this study was to compare the removal efficiency of a novel irrigation device with an extended nozzle versus a classic rinse bottle. Methods Transparent casts of the unoperated sinonasal cavity were made by 3D printing. Yogurt was used to simulate mucous. The cast filled with 5 ml yogurt was fixed in six head positions and irrigated with 120 ml, 175 ml, and 240 ml dyed water through the novel device and the rinse bottle. The irrigation efficiency was the ratio of the weight of yogurt washed away divided by the total weight of yogurt. Results The irrigation stream of a long nozzle with a side opening was different from the irrigation stream of the outlet within the nasal vestibule. The novel devices presented with continuous water stream directly upwards to the anterior part of the olfactory cleft. Depending on different head positions, it was easy for the novel devices to achieve an irrigation efficiency of 100% when the cast was irrigated with 120 ml or 175 ml water. There was still a tiny amount of yogurt left in the olfactory cleft when the cast was irrigated with 240 ml water under each head position for the rinse bottle. The irrigation efficiency was volume-dependent, and the average irrigation efficiency of the rinse bottle at 240 ml only reached 69.1%. Conclusions The novel irrigation device presented with superior nasal irrigation efficiency to the classic rinse bottle. A continuous water stream directly upwards to the anterior part of the olfactory cleft combined with an extended nozzle overcoming the flow-limiting effect of the nasal valve promotes nasal irrigation efficiency. Graphical Abstract